The Power of Scenery Frederick Law Olmsted and the Origin of National Parks. - Drabelle, Dennis (Bison Books, 2021)
The Power of Scenery tells the story of how the world's national parks came to be, with Frederick Law Olmsted's insights and energy serving to link three American jewels: Yosemite National Park, Yellowstone National Park, and Niagara Falls State Park.